Fungal enrichment of cassava peels proteins - Obadina, A.O.; Oyewole, O.; Sanni, Lateef O.; Abiola, S.S. (2006)
About 60% of the cassava produced all over the world is used for human consumption. These peels waste were found to contain 42.6% carbohydrate, 1.6% protein, 12.1% ether extract, 5.0% total ash and 22.5% crude fibre. With the advent of biotechnology approaches, there are opportunities for economic utilization of agro industrial residues such as cassava peels waste. The Microorganisms isolated from the fermenting cassava waste were Aspergillus niger, A. flavus, and A. fumigatus. These and Trichoderma sp. from soil were studied for their ability to increase the protein content of cassava peels waste.